Specific patterns of defective HSV-1 gene transfer in the adult central nervous system: implications for gene targeting. - Wood, M; Byrnes, A; Kaplitt, MG; Pfaff, D; Rabkin, S; Charlton, H (1994)
Viral vectors are a means by which genes can be delivered to specific sites in the adult central nervous system. Nevertheless, the interaction between the viral vector and cells of the nervous system, which forms the basis for specific gene transfer, is not well understood. In this study a nonreplicating defective herpes simplex virus type 1 vector, expressing the marker gene lacZ, was stereotaxically injected at varying titers into the rat central nervous system. Three sites were targeted: the caudate nucleus, dentate gyrus, and cerebellar cortex, and the resulting patterns of beta-galactosidase activity were examined. Many cells of neuronal and glial morphology, and of differing neuronal subtypes, expressed beta-galactosidase at each of the injection sites. However, beta-galactosidase activity was also detected in distant secondary brain areas, the neurons of which make afferent connections with the primary sites. This strongly suggested that the retrograde transport of defective virus was the basis for the enzyme activity observed at a distance. Moreover, retrograde transport to secondary sites was found to be highly selective and restricted to certain retrograde neuroanatomical pathways in a specific and titer dependent fashion. The pathways observed were predominantly, but not exclusively, monoaminergic in origin. This finding is supported by reports of specific tropism by HSV for monoaminergic circuits in experimental encephalitis and transneuronal tracing studies. Our observations suggest that certain functional neuronal populations, which are permissive for the retrograde transfer of defective HSV-1 vectors, might be specifically targeted for gene transfer using this approach. Conversely, a knowledge of the pathways permissive for viral uptake, retrograde transfer, and subsequent gene expression will be essential in order to predict the consequences of gene transfer using viral vectors.